Prevalence of malaria parasites in indigenous chickens and ducks in selected districts of Bangladesh (Journal of the Bangladesh Agricultural University, 2017)
Avian haematozoans are important pathogens of birds causing asymptomatic to fatal infections. The present study was undertaken to investigate the prevalence and associated risk factors of malaria parasite infections in domestic chickens and ducks in three localities namely Mymensingh, Tangail and Netrokona districts in Bangladesh. In total, 474 blood smears (266 chickens and 208 ducks) were screened for haemoprotozoan infection during the period from March, 2016 to February, 2017. Blood samples were collected from wing vein by needle puncture. The parasites were identified from Giemsa stained thin blood smears based on morphological features using standard keys. Malaria protozoa was found in 60 birds (12.7%), of which 35 were chickens (13.2%) and 25 were ducks (12.0%). Two species of blood protozoa were identified namely Leucocytozoon spp. (10.5%) and Plasmodium spp. (2.1%). The prevalence of haemoprotozoa was found high among the adults (13.9%) while it was 11.2% among young birds. Female (15.2%) was 1.46 times more susceptible than male (10.9%).The prevalence rate was highest in Netrokona (18.9%) followed by Tangail (12.2%) and Mymensingh (8.7%). In this study, the prevalence rate was highest in rainy season (18.3%), moderate in summer (10%) and less in winter season (9.3%). Present study revealed that these haemorpotozoa are capable of infecting indigenous domestic chicken and duck. Further studies should focus on characterization of the malaria parasites of indigenous chickens and ducks in Bangladesh.J. Bangladesh Agril. Univ. 15(2): 260-265, December 2017